A Reverse Analytic Inequality for the Elementary Symmetric Function with Applications - Huan-Nan Shi; Jing Zhang (Journal of Applied Mathematics)
We give a reverse inequality involving the elementary symmetric function by use of the Schur harmonic convexity theory. As applications, several new analytic inequalities for the n-dimensional simplex are established.